Afterlife: Who Takes Heart for Restart? - Georg Metzger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
The performance of young and newly founded firms depends largely to the human capital of the firm owner. The entrepreneur is therefore one of the main success factors for the firm. Yet entrepreneurs differ considerably in their background and characteristics. Particularly, founders? individual entrepreneurial experience is a property that might be crucial for firm development, though it is part of the firm?s human capital, too. Business failures, namely bankruptcies, may trigger the transition from being a novice entrepreneur to becoming an entrepreneur who is entrepreneurially experienced. About 3 percent of novice entrepreneurs who file for bankruptcy reestablish afterwards. On average, slightly more than 15 months will elapse until such ?fallen? entrepreneurs venture out anew. They differ from entrepreneurs not willing or able to take a second chance in several respects.
Keywords: M13; J23; G33; 330; Bankruptcy; Business Failure; Restart; Second Chance; Unternehmer; Konkurs; Unternehmensgründung; Schätzung; Deutschland